Literature Review: Efek Nigella Sativa terhadap Sitokin dan Sel Darah Putih sebagai Respons Imun - Nur Shinta Anggraini, Frisca (SM Institute, 2025)
Nigella sativa has long been believed to be an effective traditional medicine in curing certain diseases. Many studies have been conducted on Nigella sativa and show the various benefits provided by Nigella sativa, one of which is as an immunomodulator. The immunomodulatory effects of Nigella sativa play a role in innate immunity and adaptive immunity. White blood cells and their subtypes are related to cellular immunity because they form the cellular components of immunity, while cytokines play an important role in regulating the body's immune response by connecting innate immunity and adaptive immunity. This literature aims to examine and analyze the results of studies regarding the effect of Nigella sativa on cytokine levels and white blood cells as an immune response, as well as comparing the effects provided based on the subject of intervention. Literature review using studies published in the last 10 years (2014-2024) in international English-language journals by searching via PubMed and ScienceDirect. Study of experimental test studies on animals with certain disease conditions and clinical trials on healthy and sick humans using Nigella sativa shows a positive influence on levels of interleukins and white blood cells and their subtypes, as well as levels of other cytokines.